1999
DOI: 10.1021/jp991716n
|View full text |Cite
|
Sign up to set email alerts
|

An Absolute Sodium Cation Affinity Scale:  Threshold Collision-Induced Dissociation Experiments and ab Initio Theory

Abstract: Threshold collision-induced dissociation of Na + (L) with xenon is studied using guided ion beam mass spectrometry. The ligand L includes ethene, benzene, phenol, ammonia, acetaldehyde, acetone, and N,Ndimethylformamide. In all cases, the primary product formed corresponds to endothermic loss of the neutral ligand and the only other product observed is the result of ligand exchange processes to form NaXe + . The cross-section thresholds are interpreted to yield 0 and 298 K bond energies for Na + -L after accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

59
347
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(412 citation statements)
references
References 53 publications
59
347
6
Order By: Relevance
“…Similar to what was found by Armentrout and Rodgers for the B3LYP functional, our DFT results for sodium ion are a few kJ/mol higher than MP2, and are somewhat scattered versus MP2. [33] (They found that either MP2 or DFT/B3P86 gave somewhat better results for Na The models indicate that the amide oxygen site (O a ) is highly favored and should be metalated consistently. It is thus not surprising that the calculations of Wang et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to what was found by Armentrout and Rodgers for the B3LYP functional, our DFT results for sodium ion are a few kJ/mol higher than MP2, and are somewhat scattered versus MP2. [33] (They found that either MP2 or DFT/B3P86 gave somewhat better results for Na The models indicate that the amide oxygen site (O a ) is highly favored and should be metalated consistently. It is thus not surprising that the calculations of Wang et al…”
Section: Resultsmentioning
confidence: 99%
“…The BP86 functional has been recommended as giving slightly more accurate absolute binding energies for Na + complexes, 33 but it gives results quite similar to B3LYP in most respects, has not been suggested as being superior in terms of cation-π binding energetics, and was not used here. For complexes involving transition metals binding to aromatic ligands, it has been suggested that the MPW1PW91 functional is more accurate than B3LYP in the energetic comparision of π-binding sites with other types of sites, and specifically that B3LYP underestimates the strength of π-ring binding.…”
Section: Experimental and Computationalmentioning
confidence: 99%
“…In addition to these, the hybrid methods of DFT give very similar structural parameters compared with MP2, and the density functional vibrational frequencies and intensities are in excellent agreement with the experimental data for glycine and other amino acids system. 21 In the DFT realm, the B3LYP method appears frequently, 21,22,24 while the present calculations are carried out with DFT methods, using the B3P86 hybrid functional due to two factors: ͑i͒ it has been widely used; ͑ii͒ Armentrout and co-workers 25 found that for the Na ϩ complex the B3P86 method was somewhat better than B3LYP in terms of its calculated results agreement with more accurate theoretical values and with their experimental results. So, the B3P86 would be a reliable method to study our glycine derivatives.…”
Section: Computational Detailsmentioning
confidence: 91%
“…Basis set superposition errors (BSSE) were estimated for loose transition-state (TS) reactions using the full counterpoise (cp) method [47,48]. As for alkali metal cation systems [24,49,50], BSSE corrections for DFT calculations on H ϩ (Asn) are small, 2.0 to 3.4 kJ/mol, whereas those for MP2 calculations are larger, here 8 to 14 kJ/mol. Feller and coworkers [51,52], and Ohanessian and coworkers [53,54] have previously commented that the full counterpoise approximation to BSSE for MP2 calculations can provide worse agreement with experiment than MP2 values without BSSE corrections.…”
Section: Computational Detailsmentioning
confidence: 99%